1999
DOI: 10.1126/science.286.5444.1540
|View full text |Cite
|
Sign up to set email alerts
|

The Gelation of CO 2 : A Sustainable Route to the Creation of Microcellular Materials

Abstract: Compounds with strong thermodynamic affinity for carbon dioxide (CO(2)) have been designed and synthesized that dissolve in CO(2), then associate to form gels. Upon removal of the CO(2), these gels produced free-standing foams with cells with an average diameter smaller than 1 micrometer and a bulk density reduction of 97 percent relative to the parent material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(108 citation statements)
references
References 17 publications
1
107
0
Order By: Relevance
“…For example, we reported some years ago that the polymerizable bis-urea 8 (Scheme 1) is a potent gelling agent for apolar solvents. [8b] After photopolymerization of benzene gels and removal of the solvent by freeze-drying, an organic aerogel was obtained with very similar characteristics with respect to density and cellular size as that reported by Beckman, Hamilton et al [5] Another exciting development is the use of organogelators as template for the preparation of nanostructured materials. First Möller [9] and later also Weiss [10] and Nolte [11] prepared membranes with nanosized pores by the gel ± template ± leaching process, taking advantage of the distinct feature of organogelators to reversibly form elongated fibers with welldefined dimensions and geometry.…”
Section: Jan H Van Esch* and Ben L Feringamentioning
confidence: 72%
See 1 more Smart Citation
“…For example, we reported some years ago that the polymerizable bis-urea 8 (Scheme 1) is a potent gelling agent for apolar solvents. [8b] After photopolymerization of benzene gels and removal of the solvent by freeze-drying, an organic aerogel was obtained with very similar characteristics with respect to density and cellular size as that reported by Beckman, Hamilton et al [5] Another exciting development is the use of organogelators as template for the preparation of nanostructured materials. First Möller [9] and later also Weiss [10] and Nolte [11] prepared membranes with nanosized pores by the gel ± template ± leaching process, taking advantage of the distinct feature of organogelators to reversibly form elongated fibers with welldefined dimensions and geometry.…”
Section: Jan H Van Esch* and Ben L Feringamentioning
confidence: 72%
“…[5] The most remarkable feature of this system is that except for the organogelator and CO 2 , no other compounds or cosolvents are involved, resulting in a singlestep, very clean, and environmentally friendly method to create these materials. The essence of this work is that the authors succeeded in the design of organic gelling agents for CO 2 , that is, compounds that strongly associate and form an entangled network structure at lower temperature or pressure, but would dissolve upon increasing the temperature or pressure.…”
Section: Jan H Van Esch* and Ben L Feringamentioning
confidence: 99%
“…6, 7 Furthermore, Shi et al have reported the synthesis of new gelators that can gel supercritical CO 2 and fabrication of the porous polymers in supercritical CO 2 . 8 These studies are expected as new methods in the template-imprinting technique.…”
Section: Introductionmentioning
confidence: 99%
“…6, 7 Furthermore, Shi et al have reported the synthesis of new gelators that can gel supercritical CO 2 and fabrication of the porous polymers in supercritical CO 2 . 8 These studies are expected as new methods in the template-imprinting technique.Here we describe the preparation of porous poly(styrene) from toluene gels made by gelators using a new method, in situ precipitation and the characterization by scanning electron microscopy (SEM). The in situ precipitation is performed by replacing good solvent with poor solvent in polymer solution that is previously gelled by gelators.…”
mentioning
confidence: 99%
“…It is possible to alter the surface morphology of the substrate, and thus surface properties, if the gelation and subsequent evaporation of solvent are performed on a substrate. Hence, gel impregnation methodology could provide the low surface energies desired for fabricating superhydrophobic surfaces [19,[21][22][23][24]. Surfaces on which the contact angle of water exceeds 150°, and shows low contact angle hysteresis, are described as superhydrophobic or ultrahydrophobic [25][26][27].…”
Section: Open Accessmentioning
confidence: 99%